Here "P=\\frac{1}{2x}; Q=\\frac{1}{2x(1-x)}"
THus x=0 and x=1 are the regular points of the equation
Let's find the solution in form
"y=\\sum\\limits_{n=0}^{\\infty}a_nx^{n+r}"
Hence
"y'=\\sum\\limits_{n=1}^{\\infty}(n+r)a_nx^{n+r-1}=\\sum\\limits_{n=0}^{\\infty}(n+r+1)a_{n+1}x^{n+r}"
"y''=\\sum\\limits_{n=1}^{\\infty}(n+r)(n+r+1)a_{n+1}x^{n+r-1}=\\sum\\limits_{n=0}^{\\infty}(n+r+1)(n+r+2)a_{n+2}x^{n+r}"
Plugging it into the equation, we get
"2x(1-x)\\sum\\limits_{n=0}^{\\infty}(n+r+1)(n+r+2)a_{n+2}x^{n+r}+(1-x)\\sum\\limits_{n=0}^{\\infty}(n+r+1)a_{n+1}x^{n+r}+3\\sum\\limits_{n=0}^{\\infty}a_nx^{n+r}=0"
"\\sum\\limits_{n=0}^{\\infty}2(n+r+1)(n+r+2)a_{n+2}x^{n+r+1}-\\sum\\limits_{n=0}^{\\infty}2(n+r+1)(n+r+2)a_{n+2}x^{n+r+2}+"
"+\\sum\\limits_{n=0}^{\\infty}(n+r+1)a_{n+1}x^{n+r}-\\sum\\limits_{n=0}^{\\infty}(n+r+1)a_{n+1}x^{n+r+1}+3\\sum\\limits_{n=0}^{\\infty}a_nx^{n+r}=0"
"\\sum\\limits_{n=1}^{\\infty}2(n+r+1)(n+r)a_{n+1}x^{n+r}-\\sum\\limits_{n=2}^{\\infty}2(n+r-1)(n+r)a_{n}x^{n+r}+"
"+\\sum\\limits_{n=0}^{\\infty}(n+r+1)a_{n+1}x^{n+r}-\\sum\\limits_{n=1}^{\\infty}(n+r)a_{n}x^{n+r}+3\\sum\\limits_{n=0}^{\\infty}a_nx^{n+r}=0"
For "x^r" we get
"(r+1)a_{1}+3a _0=0"
For "x^{r+1}"
"2(r+2)(r+1)a_2+(r+2)a_1-(r+1)a_1+3a_1=0"
Comments
Leave a comment